Tapantiomyia enigmatica, new genus and species proposed for a stilt-legged and otherwise bizarre coenosiine fly (Diptera: Muscidae) from Costa Rica - Michelsen, Verner (Zootaxa, 2017)
A new monotypic genus, Tapantiomyia gen. nov., is proposed for a new species of muscid fly, T. enigmatica sp. nov., found in the Tapantí National Park, Costa Rica. It is only known by a single male specimen taken in a Malaise trap in tropical cloud forest, but deserves immediate attention because of its bizarre, stilt-legged appearance in combination with several other unique apomorphies that preclude placement in any known genus of Muscidae. Tapantiomyia enigmatica is so strange that it tend to run out to Scathophagidae rather than Muscidae in keys to families of Diptera. However, the morphology of the male genitalia provides decisive evidence for a placement in Coenosiinae, a large and diverse group of predatory Muscidae. Two tribes, Limnophorini and Coenosiini, are currently recognized within Coenosiinae, but the monophyly of Limnophorini remains uncertain. Tapantiomyia is tentatively assigned to the Limnophorini.